Establish The Influence of Government Policies Strategies on Tourism Performance In West Pokot County - Cherop Patricia, Tulel; Ombaka, Beatrice; Ann, Kariuki (International Journal of Scientific Research and Management (IJSRM), 2019)
The research focused on the influence of government policies strategies on tourism performance in west pokot county in Kenya. The study was guided objectives-policy framework, provision of infrastructure, provision of amenities and conducive taxation strategy. The theory guiding this study is consumer choice theory. The study found out government policies should have a conducive taxation strategy to attract more investors in the tourism industry. The study  recommends that the government policies should be friendly.. Areas for further research include another study be done on challenges facing domestic tourism which was not part of the study.